Speech Function of Classroom Interaction in Expository and Persuasive Writing - Aulia Ukhtin (Lembaga Riset Mutiara Akbar, 2025)
Classroom interaction plays an important role in English as a Foreign Language (EFL) writing instruction, particularly in expository and persuasive writing, where students are required to develop arguments, organize ideas logically, and negotiate meaning through language use. This study aims to analyze speech functions employed in classroom interaction and to examine the interactional roles of lecturers and students during expository and persuasive writing instruction. The data were collected from naturally occurring classroom interaction through audio recordings of lecturers and students in writing classes. The recorded interaction was transcribed verbatim and analyzed using speech function categories derived from Systemic Functional Linguistics, including statements, questions, commands, and offers. The findings indicate that classroom interaction was predominantly lecturer-centered, with statements, questions, and commands occurring most frequently, while student participation was largely limited to brief responses. Student-initiated speech functions and offers appeared infrequently, suggesting limited opportunities for collaborative negotiation of meaning. The study concludes that although lecturer-dominated speech functions support instructional clarity in writing classes, increasing opportunities for student-initiated interaction is necessary to foster more interactive and effective expository and persuasive writing instruction.